Entwicklung eines selektierenden Aalschleppnetzes - Rehme, Wolfgang (2006)
In eel catches with special small-mesh trawls the proportion of by-catch is unjustifiably high. From 2003 to 2005 eel trawls with various types of separation panels were designed, constructed, and tested under real fishing conditions. Tests were carried out using cover cod-ends and an underwater TV equipment. It was possible to reduce the amount of by-catch to one tenth of its usual amount. However, a decline of the catch efficiency for the target species eel could not be avoided. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung - Information Fishery research in 2010. Johann Heinrich von Thünen-Institut, Institut für Ostseefischerei